The Relationship between Personality Five Factor Theory and the Career Success of Executive Workers in Apparel Sector Organizations in Sabaragamuwa Province Sri Lanka - Dias, S.H.; Jayasekara, P. (Department of Human Resource Management Faculty of Management Studies and Commerce University of Sri Jayewardenepura, 2017)
Area of the Study As a significant determinant of career success of employee, this study is discussing the relationship between Personality Five Factor theory and the Career Success of executive workers in the apparel sector organizations in Sabaragamuwa province Sri Lanka. Problem of the Study There is an empirical knowledge gap in the context of the impact of personality five factor theory on the career success of employees in Sri Lanka. therefore, the problem of the study is: Does Five Factor Theory of personality affect to the career success of executives in the apparel sector organization in Sabaragamuwa province. Method of the study The data were collected from a selected sample of 122 executives in the apparel industry in Sabaragamuwa province Sri Lanka by administrating a structured questionnaire, which consisted of 63 questions/ statements with 5 points scale. The data analyses included the univariate and bivariate analyses. Findings of the Study The authors found that some of the factors have strong positive relationship and some have negative relationship and some haven’t any relationship with career success of executives in apparel sector organizations in Sabaragamuwa province, Sri Lanka. Extraversion and Conscientiousness have strong positive relationship with career success of the executives and Agreeableness and Neuroticism have negative relationship with the executives of the apparel sector organizations. However, there is no any relationship in Openness to experience with career success of the executives. Conclusion of the Study Future research based on the current theoretical model can investigate the relationship of personality with other work related behaviors and outcomes. The empirical confirmation of this conceptual model is another area of future research. Future research should attempt to replicate these results and develop process models that may explain why conscientiousness and Extraversion have such apparently enduring associations with career success.
Keywords: Personality Five Factors, Career Success, Executives, Apparel Sector Organizations